Selective Suprascapular and Axillary Nerve Block Versus Interscalene Plexus Block for Pain Control After Arthroscopic Shoulder Surgery: A Noninferiority Randomized Parallel-Controlled Clinical Trial. Issue 7 (1st October 2018) - Neuts, Anneleen; Stessel, Björn; Wouters, Patrick F.; Dierickx, Carl; Cools, Wilfried; Ory, Jean-Paul; Dubois, Jasperina; Jamaer, Luc; Arijs, Ingrid; Schoorens, Dirk
Abstract : Background and Objectives: This randomized trial aimed to assess if a combined suprascapular-axillary nerve block (SSB) is noninferior (margin = 1.3 on a 0- to 10-point scale) to interscalene block (ISB) in treating pain after arthroscopic shoulder surgery. Secondary end points included opioid consumption, dyspnea, discomfort associated with muscle weakness, and patient satisfaction. Methods: One hundred patients undergoing arthroscopic shoulder surgery were randomized to receive ultrasound-guided ISB (n = 50) or SSB (n = 50). Pain intensity at rest, dyspnea, and discomfort were recorded upon arrival in the recovery room, discharge to the ward, and at 4, 8, and 24 hours after surgery. Piritramide consumption was recorded for the first 24 hours. Patient satisfaction was assessed on the second postoperative day. Results: During the first 4 hours after surgery, the difference in mean pain score between SSB and ISB was higher than 2.5 (±0.8). The difference gradually decreased to 1.1 (±1.0) at 8 hours before resulting in noninferiority during the night and at 24 hours. Piritramide consumption was significantly higher in the SSB group in the first 8 hours. The incidence of dyspnea and discomfort was higher after ISB. Treatment satisfaction was similar in both groups. Conclusions: Suprascapular-axillary nerve block is inferior to ISB in terms of analgesia and opioid requirement in the immediate period after arthroscopic shoulder surgery but is associated with a lower incidence of dyspnea and discomfort. The difference in pain and opioid consumption gradually decreases as the blocks wear off in order to reach similar pain scores during the first postoperative night and at 24 hours. Clinical Trial Registration: This study was registered at ClinicalTrials.gov, identifier NCT02415088 .